1997
DOI: 10.1207/s15327809jls0601_5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Science Assessment: A New Approach for Investigating Conceptual Change

Abstract: Journal of the Learning SciencesPublication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In the meantime, the ninth-grade students scored lowest on the items related to concepts in electricity, a finding which corresponds to the many studies that reveal that electricity concepts are difficult for children to learn, especially the concepts of circuit, current, and electrical energy (Shipstone, 1988;Garnett & Treagust, 1992;Furio & Guisasola, 1998). We discovered two common misconceptions regarding electricity in our study, which have also been revealed by many researchers (Magnusson, Boyle & Templin, 1997;Osborne, 1983;Russell, 1980;Shipstone, 1984): Students thought that the bulb in a series nearest the positive electrode would light first (Appendix, item 18), and that two bulbs together use more electricity than a single bulb (Appendix, item 17).…”
Section: Discussionsupporting
confidence: 86%
“…In the meantime, the ninth-grade students scored lowest on the items related to concepts in electricity, a finding which corresponds to the many studies that reveal that electricity concepts are difficult for children to learn, especially the concepts of circuit, current, and electrical energy (Shipstone, 1988;Garnett & Treagust, 1992;Furio & Guisasola, 1998). We discovered two common misconceptions regarding electricity in our study, which have also been revealed by many researchers (Magnusson, Boyle & Templin, 1997;Osborne, 1983;Russell, 1980;Shipstone, 1984): Students thought that the bulb in a series nearest the positive electrode would light first (Appendix, item 18), and that two bulbs together use more electricity than a single bulb (Appendix, item 17).…”
Section: Discussionsupporting
confidence: 86%
“…Results showed that most predictions came close to fitting the empirical data, except C-character 12. C-characters 12-1 (two bulbs share current equally) and 12-2 (two bulbs share current unequally) are important alternative conceptions (Chiu & Lin, 2005;Magnusson et al, 1997), but their percentages in cross-grade survey were too low (5% to 15.8%). Because this result was not identical to other results, Lin and Chiu (2009a) suggested that the cross-grade survey items should be revised.…”
Section: Cladistics Approach In Conceptual Evolution and Its Predictimentioning
confidence: 99%
“…These models were also reflected in other countries (Butts, 1985;Gott, 1984;Shen, Gibbons, Wiegers, & McMahon, 2007;Shepardson & Moje, 1994;Shipstone, 1985). Based on previous studies, Magnusson, Boyle, and Templin (1997) divided the clashing current model into a cross current model, similar to the alternating current from two battery poles. The current attenuation model was divided into an attenuation model reflecting the uneven brightness of two light bulbs and a shared model reflecting the equal brightness of two light bulbs.…”
Section: Student Ideas Of Electricity and Related Cross-age Studiesmentioning
confidence: 99%
“…Authors within a sociocultural or situative perspective have pointed to the benefits of focusing on activity systems when studying processes of learning and development, as a complement to more traditional studies of individual learners (Greeno, 2006;Kelly & Green, 1998;Magnusson, Templin, & Boyle, 1997;Rogoff & Chavajay, 1995;Säljö, 1997). Specifically, such a perspective opens up alternative ways of dealing with contextual issues of learning by including social interaction, communication, and sociocultural artifacts as constitutive parts of cognition (Dewey, 1925(Dewey, /1958Vygotsky, 1978, p. 89).…”
Section: Theoretical Backgroundmentioning
confidence: 99%